Pengaruh Kejelasan Sasaran Anggaran, Penggunaan Siskeudes, Kompetensi SDM terhadap Akuntabilitas Pengelolaan Dana Desa Dimoderasi Komitmen Organisasi - Shanny Logo Buke; Edy Sujana; I Gusti Ayu Purnamawati (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the effect of budget target clarity, the use of Sistem Keuangan Desa (Siskeudes), and human resource competence on the accountability of village fund management, with organizational commitment as a moderating variable. This study employed a mixed methods approach through quantitative and qualitative methods. The population consisted of all 160 villages in Kupang Regency. The sampling technique used purposive sampling, resulting in 43 villages across five districts. The total number of respondents was 215, consisting of village heads, village secretaries, heads of affairs, section heads, and chairpersons of the Village Consultative Body. Data were collected through questionnaires, interviews, and documentation, and then analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that budget target clarity had a positive and significant effect on the accountability of village fund management. The use of Siskeudes also had a positive and significant effect on the accountability of village fund management and was the most dominant variable in improving accountability. Human resource competence was proven to have a positive and significant effect on the accountability of village fund management. In addition, organizational commitment was able to strengthen the influence of budget target clarity, the use of Siskeudes, and human resource competence on the accountability of village fund management. These findings indicate that improving village fund accountability is influenced by technical aspects, the quality of village officials, and organizational commitment in carrying out duties transparently, professionally, and responsibly.